EFISIENSI REPRODUKSI SAPI PERAH FRIESIAN HOLSTEIN (Studi kasus Di Peternakan Bapak Nur Trianto Desa Ngaglik Kecamatan Srengat Kabupaten Blitar) - Nita Opi A.K (Universitas Islam Balitar, 2016)
This research have done at Mr. Nur Trianto ’s dairy cow breeding, which placed at Ngaglik village, Srengat districk, Blitar, began at 11th until 24th June 2012. This research in order to know the CR, S/C, and NRR grade of his dairy cows.The materials of this research are 30 dairy cows Friesian Holstein (FH) with 63,3% as CR valve, so the conception number is on the standart. Then, S/C value is 1,5, this value shows that S/C value in this breeding is very good. And the last is NRR value, it ’s 63,3%, it means that 63,3% or 19 dairy cows do not want be inseminated again after the farmer doing artificially insemination. The result of research that Mr. Nur Trianto ’s breeding has dairy cows with a good fertility and standart in farming management. The suggest for this research is the breeder should always make the note of his cattle ’s reproduction complete, in order to be able to manage his breeding easier.Key Word: CR, S/C, NRR